Micropropagation of Echinacea purpu rea using lateral shoots and seeds as explants - Loaiza, Jorge (2004)
To generate a micropropagation protocol for the medicinal plant Echinacea purpurea, 0.75, 1.5, 3, and 5% of NaOCl with 10, 15, 20, 25, and 30 min. immersion times were evaluated for disinfection. Results showed no contamination when 5% of NaOCl was used in combination with 25 min immersion. Initially, the basal medium of Murashigue and Skoog (1962) was assessed at 25, 50, 75% and 100% salts strength. The halfsalts strength (MS/50) proved to be the most effective one, resulting in better growth of explants; therefore, it was supplemented with 0.1, 0.5, and 1 mg l-1 of 6-benzylaminopurine (BAP) for in vitro shoot proliferation. A proliferation rate of 12 new shoots per explant was obtained when the medium was supplemented with 0.5 mg l-1 of BAP. The effect of IAA on root induction was also studied. A rooting percentage of up to 100% with 45% roots >3 cm, was achieved by the use of 3 mg l-1 of IAA. After 8 weeks of acclimatization, survival of rooted shoots in the greenhouse was 100%.